استقلالية القضاء في الجزائر على ضوء التعديل الدستوري لسنة 2020 - محمد ياسين محامدية; محمد إسلام بوقفة (My University, 2022)
Abstract: The constitutional amendment of 2020 is a qualitative leap in the independence of the judicial institution especially article 180 of the Constitutional Amendment which freed the Supreme Council of the Judiciary from the dominance of the executive institution removing the President of the Republic and the Minister of Justice from the composition of the Supreme Council of the Judiciary is tantamount to The first step in the way of the independence of the judiciary and the practical embodiment of the principle of separation of powers. However there is still a long way to go to gain the independence of the judicial institution. The composition of the Supreme Judicial Council continues to suffer from a defect within it with the presence of persons who do not belong to these The judicial institution is within it and the rest of the constitutional institutions have imposed on it which brings us back to the dialectic of the extent to which the principle of separation of powers is actually enshrined in this intervention. ............................ ملخص المذكرة: يعتبر التعديل الدستوري لعام 2020 قفزة نوعية في مجال استقلالية المؤسسة القضائية، خصوصا المادة 180 من التعديل الدستوري التي حررت المجلس الأعلى للقضاء من هيمنة المؤسسة التنفيذية، فإبعاد رئيس الجمهورية ووزير العدل عن تشكيلة المجلس الأعلى للقضاء يعد بمثابة الخطوة الأولى في طريق استقلالية القضاء والتجسيد العملي لمبدأ الفصل بين السلطات. لكن ومع ذلك لا زال الطريق طويلا للوصول إلى استقلالية المؤسسة القضائية. فلا زالت تشكيلة المجلس الأعلى للقضاء تعاني من خلل في داخلها، وذلك بتواجد أشخاص لا ينتمون إلى هذه المؤسسة القضائية بداخلها ، وقد فرضتهم بقية المؤسسات الدستورية عليها مما يعيدنا مرة أخرى إلى جدلية مدى التكريس الفعلي لمبدأ الفصل بين السلطات في ظل هذا التدخل.